Development of a Model for Urban Governance Based on Citizen Participation - Elham Agherian; Mostafa Nabatinejad; Ali Zackery (Strategic Research on Social Problems)
Introduction:Urban planning has undergone significant transformations throughout history marked by distinct eras characterized by shifts in planning principles, approaches, and objectives. In recent years, citizens’ participation and democratization of urban management have gained considerable attention and importance. It has become evident that imposing large-scale urban projects on communities without their input or involvement can lead to severe backlash. Traditional methods, such as offline consultations, co-design workshops, and surveys, have facilitated architects and planners in understanding and engaging with communities. However, advancements in technology and online platforms have opened up new avenues for harnessing the collective intelligence of entire cities and communities in the urban planning and design process. The presence of strong democratic institutions, respect for human rights, and participatory accountable governance are essential for enhancing people's lives in a sustainable manner. In an increasingly urbanized world, these factors contribute to unlocking the potential of cities, particularly through improved urban service delivery. Well-managed cities with enhanced services promote peace, security, and greater investment in human capital, thereby driving economic growth. Municipal governments that possess adequate resources and are accountable are more likely to provide timely and efficient services. Collaborative efforts among different levels of government and civil society contribute to optimizing service delivery. Transparent, accountable, and democratic institutions play a vital role in facilitating community participation in demanding and designing improved service delivery. Various models have been developed to expand citizen engagement in urban management. Cities should strive for systemic changes in decision-making processes related to urban planning, incorporating deliberative and democratic procedures. This paper introduced a novel model for citizen participation in urban management.  Materials & Methods:This study adopted a qualitative, interpretive, applied, and cross-sectional research design. The statistical population consisted of municipality managers, NGO managers, and urban scholars in Isfahan City. A total of 15 experts were selected from this population using the snowball sampling technique and were subsequently interviewed. The collected data were analyzed inductively using a content analysis approach. To ensure the reliability of the analysis, 5 interviews were randomly selected and subjected to thematic analysis once again. This process aimed to validate the findings.To further enhance the robustness of the results, a fuzzy Delphi method was employed, involving 10 municipality managers and 5 academicians. The participants were requested to evaluate the relevance and significance of the identified themes, aiming to achieve a fuzzy consensus. Their suggestions and feedback were incorporated into the final model, thereby strengthening the overall quality of the findings. Discussion of Results & Conclusion:The data for this study were collected through semi-structured interviews and analyzed using thematic analysis. The analysis revealed 55 basic themes, 15 organizing themes, and 5 global themes. The content validity ratio, which exceeded the threshold of 60%, confirmed the validity of the results. Furthermore, the results of the fuzzy Delphi method, after defuzzification, indicated unanimous agreement among the experts, thus affirming the reliability of the findings.Based on the research outcomes, a spiral-fractal model for citizen participation in urban governance was proposed. The model comprised 5 key elements: citizens, cituards, citgentsia, citally, and cityors. Cituards were citizens, who demonstrated slightly higher levels of engagement than the average citizen. They actively monitored the city, provided reflections, and followed up on their suggestions. Citgentsia were individuals, who contributed novel ideas and offered original recommendations to benefit the city. When the ideas of the Citgentsia were put into practice, they were referred to as citally within this model. The final level of the spiral-fractal model was occupied by cityors, who were involved, either officially or unofficially, in the theoretical and practical dimensions of all aspects of urban management.